The absent musculocutaneous nerve: A systematic review - Dawn D. Hunter; Matthew J. Zdilla (Elsevier, 2021)
The musculocutaneous nerve is occasionally absent in humans. Accordingly, there may be unforeseen clinical implications regarding the atypical innervation of the musculature otherwise supplied by the musculocutaneous nerve. Case reports and prevalence studies have detailed the absence of the musculocutaneous nerve; however, a systematic review has not been conducted. Therefore, this report utilized Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines to identify 24 manuscripts for qualitative synthesis, including 16 cases and eight cross-sectional studies detailing 482 limbs from 241 individuals. The prevalence of the absence of the musculocutaneous nerve among limbs ranged from 1.66% (1:60 limbs) to 13.33% (4:30 limbs). However, females were under-represented among reports-only 8.7% (21:241) of the population studied. The review identified that in the absence of the musculocutaneous nerve, the biceps brachii, brachialis, and, when present, accessory head of the biceps brachii were almost always innervated by branches of the median nerve. The coracobrachialis was innervated by branches from, most commonly, the lateral cord and less commonly, the lateral root of the median nerve or a recurrent branch from the median nerve. In a typical median nerve injury, clinical manifestations would include motor and sensory deficits in the wrist and hand. However, a high median nerve injury occurring in the absence of a musculocutaneous nerve would have an atypical clinical presentation-specifically, weakness in shoulder and elbow flexion, weakness in supination, and also cutaneous sensory loss to the lateral forearm in addition to the typical median nerve palsy affecting the wrist and hand.